2017
DOI: 10.3168/jds.2016-11510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding warm-season annuals with orchardgrass on ruminal fermentation and methane output in continuous culture

Abstract: A 4-unit, dual-flow continuous culture fermentor system was used to assess nutrient digestibility, volatile fatty acids (VFA) production, bacterial protein synthesis, and methane (CH) output of warm-season annual grasses. Treatments were randomly assigned to fermentors in a 4 × 4 Latin square design using 7 d for adaptation to treatment and 3 d for sample collection. Treatments were (1) 100% orchardgrass (Dactylis glomerata L.; ORD); (2) 50% orchardgrass + 50% Japanese millet [Echinochloa esculenta (A. Braun) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
3
15
2
1
Order By: Relevance
“…Ruminal NH 3 -N concentration was greater (P < 0.01) for FK compared with the other forages (Table 4), possibly as a result of highest (P < 0.05) true CP digestibility (Table 3). In agreement with the current study, Dillard et al (2017) also found a positive relationship between true CP digestibility and effluent NH 3 -N concentration when dual-flow continuous culture fermenters were fed 100% orchardgrass. Nevertheless, the accumulation of NH 3 -N in the fermenter fluid not only depends upon the extent of CP digestibility but also on the rate of N utilization by ruminal bacteria (Bach et al, 1999).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Ruminal NH 3 -N concentration was greater (P < 0.01) for FK compared with the other forages (Table 4), possibly as a result of highest (P < 0.05) true CP digestibility (Table 3). In agreement with the current study, Dillard et al (2017) also found a positive relationship between true CP digestibility and effluent NH 3 -N concentration when dual-flow continuous culture fermenters were fed 100% orchardgrass. Nevertheless, the accumulation of NH 3 -N in the fermenter fluid not only depends upon the extent of CP digestibility but also on the rate of N utilization by ruminal bacteria (Bach et al, 1999).…”
Section: Methodssupporting
confidence: 92%
“…Although FK treatment had increased (P < 0.05) true CP digestibility, which led to an increase (P < 0.01) in ruminal NH 3 -N concentration, it was not followed by improvements in N utilization since bacterial efficiency showed no concurrent increase. Bacterial efficiency averaged 7.84 g of bacterial N per kilogram of OM truly digested, which agrees with data reported by Dillard et al (2017), who found a bacterial efficiency average of 7.32 g in dual-flow continuous culture when fermenters were fed diets containing 100% orchardgrass or Least squares means within the same row with different superscripts differ (P < 0.05).…”
Section: Methodssupporting
confidence: 89%
“…However, Ingram (2014) found that when grazed, canola (Brassica napus) had a mean seasonal herbage biomass of 873 kg DM/ha. Dillard et al (2017a) reported greater seasonally accumulated herbage biomass during the fall in monocultures of canola, rapeseed (B. napus L.), and turnip (B. rapa L.) than ARG (1,023 and 242 kg DM/ha, respectively). No difference in fall accumulated herbage biomass was observed among brassica species.…”
Section: Forage Production and Qualitymentioning
confidence: 97%
“…No difference in fall accumulated herbage biomass was observed among brassica species. Ingram (2014) and Dillard et al (2017a) reported CP concentrations of multiple brassica forage species ranging from 20% to 30%. Furthermore, NDF and ADF concentrations were considerably lower than similar CSA grasses, with brassicas having 46% and 22% less NDF and ADF, respectively, than ARG (19% vs. 35% NDF and 14% vs. 18% ADF, respectively; Dillard et al, 2017a).…”
Section: Forage Production and Qualitymentioning
confidence: 99%
“…Depending on the CCF apparatus, the volume‐to‐feed ratio of each system varies tremendously. For example, Rusitec systems use 20 g substrate/day per 0.7 L = 29 g/L (Hristov et al, ), while the Dillard et al () system used 60 g substrate/day per 1.1 L = 55 g/L. This results in different dilution rates and retention times within each system, causing large discrepancies among different systems even when using the same diet ingredients.…”
Section: Discussionmentioning
confidence: 99%